Development of a Mobile-Based Ruminant Livestock Monitoring System at Sarwa Adem Mulya Multi-Party Cooperative - M Syauqi Haris; Risqy Siwi Pradini; Achmad Jaelani Rusdi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The Sarwa Adem Mulya Multi-Party Cooperative, located in Dusun Petung Wulung, Toyomarto Village, Singosari District, Malang Regency, oversees more than 80 ruminant livestock farmers with 13 key livestock management activities. Until now, record-keeping has been conducted semi-manually using Google Forms, which presents several challenges: slow processing, low accuracy, and limited accessibility for farmers with low digital literacy. This community service program aims to develop a mobile application based on a Progressive Web App (PWA) that facilitates real-time livestock recording, integrates with the cooperative’s dashboard, and can be used offline. The implementation methodology includes socialization, training, technology deployment, mentoring, and evaluation. As a result, over 70% of cooperative members participated in the training, and 57 farmers actively used the application, recording more than 1,200 activity entries within the first three months. Evaluation indicates a 25% improvement in data recording accuracy, a significant reduction in data duplication, and the availability of an analytical dashboard for the cooperative. This program supports SDG (Sustainable Development Goals) 2 (Zero Hunger), SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), as well as SDG 13 and 15 (Climate Action and Life on Land).